2009
DOI: 10.1051/kmae/2009021
|View full text |Cite
|
Sign up to set email alerts
|

Current ideas on methodological approaches in European crayfish conservation and restocking procedures

Abstract: Key-words: conservation, management, indigenous crayfish species (ICS), restockingThe present paper deals with reintroductions or restocking as a management strategy for the indigenous crayfish species (ICS) in Europe. The suitability of the target habitat, the stocking material and the stocking procedure itself are paramount during any reintroduction measure: apart from general water quality and structural parameters, a suitable habitat is ideally geographically isolated from other surface waters and human ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…Management and conservation of ICS require information about NICS, e.g. the safe distance for reintroduction, determination and monitoring of crayfish distribution and abundance, and detection of new introductions (Souty-Grosset and Reynolds, 2009;Gherardi et al, 2011) as well as the rate of NICS spread (Peay and Füreder, 2011;Perdikaris et al, 2012). Propagule pressure of NICS is recognized as one of the main factors of establishment (Capinha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Management and conservation of ICS require information about NICS, e.g. the safe distance for reintroduction, determination and monitoring of crayfish distribution and abundance, and detection of new introductions (Souty-Grosset and Reynolds, 2009;Gherardi et al, 2011) as well as the rate of NICS spread (Peay and Füreder, 2011;Perdikaris et al, 2012). Propagule pressure of NICS is recognized as one of the main factors of establishment (Capinha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The main threats to the species are the crayfish plague, the alien crayfish species and the modification and pollution of its natural environment (Souty-Grosset et al, 2006). Due to the high amount of manmade crayfish translocations and stockings, the natural genetic structure of the species has been efficiently shattered, mixed and diminished in large parts of the Europe (Souty-Grosset and Reynolds, 2009;Schrimpf et al, 2011Schrimpf et al, , 2014. The narrow diversity may have affected its ability to survive in the changing environment.…”
Section: Introductionmentioning
confidence: 99%
“…The maintenance of the variability improves the species possibilities to adapt to the changing environmental conditions (Kozák et al, 2011) including the possibilities to resist new diseases. Recently, it has been recommended that the re-establishment programs which aim to restore the native crayfish in certain areas, should also take into account the genetic diversity and variability of the donor population (Souty-Grosset and Reynolds, 2009), but also, whenever possible, to use the locally adapted populations from a close geographic distance to retain the local diversity of the species (Souty-Grosset and Reynolds, 2009;Kozák et al, 2011;Schrimpf et al, 2011Schrimpf et al, , 2014. The crayfish plague (Aphanomyces astaci) has been reported to have entered the Finnish waters in the year 1893 (Järvi, 1910;Alderman, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies that relate crayfish distribution and movement to river impoundments such as culverts have focused primarily on the potential of culverts and weirs to limit the geographical spread of introduced species of crayfish (Light, 2003;Kerby et al, 2005;Dana et al, 2011;Foster and Keller, 2011;Frings et al, 2013;Maceda-Veiga et al, 2013), thus further highlighting the potential ability of these structures to negatively impact native species of crayfish. Culverts can restrict movement and limit dispersal of crayfish, as well as other aquatic animals by causing the elevation of water velocity, increasing channel homogeneity and alteration of river bed structure, or creating direct barriers through the positioning of elevated culvert outlets and mini weirs (Bubb et al, 2008;Souty-Grosset and Reynolds, 2009;Franklin and Bartels, 2012). More specifically, it has been shown that crayfish dispersal is closely linked to water flow patterns (Acosta and Perry, 2001), and that water velocities as low as 2 cm·s −1 can impede upstream movement of native North American crayfish Orconectes propinquus (Girard, 1852), andO.…”
Section: Introductionmentioning
confidence: 99%